Waste management: ecological and technological aspects study aid - Osipova geochemist and geoecologist Associate Professor of Tomsk Polytechnic University, Candidate of chemical sciences; Matveenko linguist Professor of Tomsk Polytechnic University, Doctor of Philology; Mezhibor geoecology, specialist in the field of environmental Geochemistry associate Professor of Tomsk Polytechnic University; Azarova geochemist Associate Professor of Tomsk Polytechnic University, candidate of geological and mineralogical sciences (TPU Publishing House, 2023)
The aid is designed in accordance with the curricula of Bachelor and Master training for the profile of "Environment and Natural Resource Management" and reflects the current state of legislation and engineering techniques of processing in the sphere of waste management. The study aid includes methodical recommendations for practical works in the form of calculation problems. It is intended for the students trained in the Bachelor profiles 05.03.06 "Environment and Natural Resource Management", the Master profile 05.04.06 "Environment and Natural Resource Management. Environmental Engineering and Sustainability" when studying the discipline "English for Communication in the Professional sphere" as well as for international students studying at Tomsk Polytechnic University in the same profiles.